The Extent of It Infrastructure Development and Its Relation to the Efficiency of Accounting Information Systems-An Applied Study in Palestinian Governmental Higher Education Institutions in Gaza Strip - Hani Daloul, Mahmoud (Finance and Business Economies Review, 2019)
This study aims to measure the extent of realizing efficiency of accounting information system in light of development Information Technology (IT) infrastructure in the Palestinian governmental institutions of higher education in the Gaza Strip. The study concluded with several results, the most important of which are that: there is a strong, positive, and significantly correlative relation between the availability of IT infrastructure including its five resources (physical, software, human, database, communication and network) and the efficiency of accounting information systems. There is also a medium, positive, and significantly correlative relation between the availability of IT infrastructure and the efficiency elements of accounting information systems (input, processing, output). The study arrived at a set of recommendation, the most important of which are: the necessity to consider developing IT infrastructure especially the human resource aspect. Furthermore, extra efforts should be exerted to realize the efficiency of accounting information systems through working on its development and increasing its capacity for the optimum use of available resources.